Comparison of Milan and UCSF criteria for liver transplantation to treat hepatocellular carcinoma - Unek, Tarkan (Baishideng Publishing Group Co., Limited, 2011)
AIM: To assess the validity of the Milan and University of California San Francisco (UCSF) criteria and examine the long-term outcome of orthotopic liver transplantation (OLT) in patients with hepatocellular carcinoma (HCC) in a single-center study. METHODS: This study is a retrospective review of prospectively collected data. Between 1998 and 2009, 56 of 356 OLTs were performed in patients with HCC. Based on pathological examination of liver explants, patients were retrospectively categorized into 3 grou-ps: Milan + (n = 34), Milan -/UCSF + (n = 7) and UCSF - (n = 14). RESULTS: Median follow-up period was 39.5 (1-124) mo. The 5-year overall survival rates in the Milan +, Milan -/UCSF + and UCSF-groups were 87.7%, 53.6% and 33.3%, respectively (P < 0.000). Within these groups, tumor recurrence was determined in 5.8%, 14.3% and 40% of patients, respectively (P < 0.011). Additionally, the presence of microvascular invasion within the explanted liver had a negative effect on the 5-year disease free survival (74.7% vs 46.7%, P < 0.044). CONCLUSION: The Milan criteria are reliable in the selection of suitable candidates for OLT for the treatment of HCC. For cases of OLT involving living donors, the UCSF criteria may be applied.